Management of Acute Coronary Syndrome Indonesia: Insight from One ACS Multicenter Registry - Dafsah Arifa Juzar; Akhtar Fajar Muzakkir; Yose Ramda Ilhami; Nahar Taufiq; Tri Astiawati; I Made Junior R A; Miftah Pramudyo; Andria Priyana; Afdhalun Hakim; Setyasih Anjarwani; Jusup Endang; Bambang Widyantoro (The Indonesian Heart Association, 2025)
In “Management of Acute Coronary Syndrome in Indonesia: Insight from One ACS Multicenter Registry” (Indonesian Journal of Cardiology, 43(2), 45-55. https://doi.org/10.30701/ijc.1406), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1406. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1406